ANALISIS PEMASARAN BAWANG MERAH LEMBAH PALU DI DESA WOMBO KALONGGO KECAMATAN TANANTOVEA KABUPATEN DONGGALA - Hj. Hadayani, Syukrianto As Samana (AGROTEKBIS, 2015)
This study aims to determine the form of marketing channels, the amount of the marketing margin, part of the price received by farmers and the efficiency of commodity marketing onion valley of Palu in the village of Wombo Kalonggo Tanantovea District of Donggala. This research was conducted in the village of Wombo Kalanggo, District of Donggala Tanantovea. Take the 30 respondents from 96 farmers using simple random sample method (Simple Random Sampling). In addition to determining the respondent trader in use methods of assessment respondents (Tracing Sampling Method). Based on the results of research, there are two forms of marketing channels in the village Wombo Kalonggo, the channel I : Farmers - traders - retailers - consumers.Channel II : Farmers - retailers - consumers. Marketing margins onion valley of Palu obtained for the first channel Rp. 4000.00 and total marketing margin onion valley ofPalu obtained for the second line is Rp. 3.000,00. Any part ofthe price received bythe farmeronthe firstlineis 4.33%. Any part ofthe price received bythe farmeronthe secondlineis 3.62%. I channel marketing efficiency value of 4.33% and to channel II at 3.62%. From both the efficiency of the channels I and II are the most efficiency is channel II.